Biodiesel production from wild mustard (Sinapis Arvensis) seed oil using a novel heterogeneous catalyst of LaTiO3 nanoparticles. (1st January 2022) - Rezania, Shahabaldin; Mahdinia, Saeideh; Oryani, Bahareh; Cho, Jinwoo; Kwon, Eilhann E; Bozorgian, Alireza; Rashidi Nodeh, Hamid; Darajeh, Negisa; Mehranzamir, Kamyar
Highlights: The heterogeneous catalyst used for conversion of wild Mustard seed oil to biodiesel. The biodiesel yield was 92.21% at a temperature of 80 °C in 60 min. FAMEs yield decreased to from 95% to 87% after eight cycles. Abstract: This study synthesized a novel heterogeneous catalyst using lanthanum titanium dioxide (LaTiO3) nanoparticles via co-precipitation and calcination processes. The proposed LaTiO3 NPs were used for biodiesel production from wild mustard seed oil in the presence of methanol. The solid catalyst material was characterized by Fourier-transform infrared spectroscopy (FT-IR), X-ray diffractometry (XRD), and scanning electron microscopy (SEM). The process of trans-esterification was affected by the reaction conditions, such as the molar ratio of alcohol to oil (4:1), amount of catalyst (100 mg), reaction time (60 min), and temperature (80 °C). Under optimized conditions, the highest rate of biodiesel was 92.21% at 80 °C for 60 min in the presence of LaTiO3 NPs. Finally, the catalyst showed a maintained performance for at least five runs and up to eight runs. This result implied that the reported catalyst has a high potential to produce biodiesel at a reasonable cost and appropriate reaction conditions.